2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944322
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of progression of fatigue conditions in biceps brachii muscles using surface electromyography signals and complexity based features

Abstract: Muscle fatigue is a neuromuscular condition where muscle performance decreases due to sustained or intense contraction. It is experienced by both normal and abnormal subjects. In this work, an attempt has been made to analyze the progression of muscle fatigue in biceps brachii muscles using surface electromyography (sEMG) signals. The sEMG signals are recorded from fifty healthy volunteers during dynamic contractions under well defined protocol. The acquired signals are preprocessed and segmented in to six equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 17 publications
(20 reference statements)
2
27
2
Order By: Relevance
“…The present findings showed that fatigue results in a significant loss in sEMG complexity. Consistently, previous research has reported decreases in neuromuscular complexity under fatigued conditions in a variety of neuromuscular outputs such as sEMG [16,17] and muscle torque time series [26,27]. Changes in the complexity of the dynamics of a system occur due to changes in the number of active constituents in a system [1].…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…The present findings showed that fatigue results in a significant loss in sEMG complexity. Consistently, previous research has reported decreases in neuromuscular complexity under fatigued conditions in a variety of neuromuscular outputs such as sEMG [16,17] and muscle torque time series [26,27]. Changes in the complexity of the dynamics of a system occur due to changes in the number of active constituents in a system [1].…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies on muscle torque complexity have reported α values similar to those observed for sEMG, though notably different SampEn values (~0.5) [26,27]. Other investigations on sEMG complexity, however, reported SampEn values similar to those observed [4,17]. This may be due to potential differences between sEMG and muscle torque complexity.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The high value of spectral entropy corresponds to more complex and less regular property. 8,9 Spectral entropy is modified to obtain the instantaneous spectral entropy and is given as…”
Section: Ispenmentioning
confidence: 99%